A comparative cephalometric study for adult operated cleft palate and unoperated cleft palate patients. Issue 7 (September 2015) - Ye, Bin; Wu, Yeke; Zhou, Yuqiao; Jing, Huan; Hu, Jing; Zhang, Guozhi
Abstract Objective To determine the effects of a cleft deformity unilateral cleft lip and palate (UCLP) and the subsequent surgical interventions on maxillary growth. Materials and methods This retrospective study evaluated the lateral cephalograms of 3 groups of individuals: 40 adult patients with ULCP who underwent surgery for both lip and palate; 40 adult patients with ULCP who underwent surgery for lip only; and 40 age- and gender-matched noncleft controls. Differences in jaw morphology among them were analyzed statistically. Results Adult UCLP patients in both groups showed maxillary hypoplasia in anteroposterior and vertical directions compared with noncleft control adults. Significant differences (p ≤ 0.01) in the ANB (subspinale–nasion–supramentale angle), NA-FH (the angle formed between Frankfort horizontal plane and the plane from nasion to subspinale), MP-FH (the angle formed between mandibular plane and Frankfort horizontal plane), and GoMe/SN (the ratio between length of mandibular body and length of anterior cranial base) were found between the two UCLP patient groups. Although maxillary growth in the two UCLP groups was less than that in the noncleft control group, the anteroposterior growth in the UCLP patients with palatoplasty was even less than that in the UCLP patients with unoperated palate. Conclusions There may be an intrinsic deficiency of maxillary anteroposterior and vertical development in UCLP patients compared with the noncleft controls. Palatoplasty can further limit the anteroposterior growth of maxilla but has no detrimental effect on maxillary vertical development. The mandible is rotated clockwise after palatoplasty in UCLP patients.